Pemeriksaan C-Reactive Protein sebagai Skrining Penanda Inflamasi dan Pemberian Makanan Tambahan pada Anak Stunting di Kelurahan Penfui Kota Kupang - Ni Ketut Yuliana Sari; Agnes Rantesali; Adrianus Ola Wuan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Malnutrition over a long period of time as a cause of stunting, can cause toddlers to be susceptible to infection. C-Reactive Protein (CRP) is one of the biomarkers of inflammation as a cause of infection. Community service activities in the form of providing additional food to stunted and malnourished children for 90 days in the Penfui village of Kupang City through the Orang Tua Anak Asuh programme (OTA2S), as well as CRP testing. Each lecturer team has 2 foster children in this programme. A total of 15 children / toddlers were successfully sampled for CRP testing, and obtained 100% non-reactive. Anthropometry of 2 toddlers as foster children showed different results. Toddler No.1 showed a decrease in weight in the third month by 0.5 kg, but an increase in height by 1, 9 cm and LiLa by 0.2 cm. In toddler No.2 there was an increase in body weight by 0.25 kg, an increase in height by 1.2 cm, but a decrease in LiLa by 0.7 cm.